ANALISIS RISIKO KECELAKAAN KERJA MENGGUNAKAN METODE HAZARD IDENTIFICATION, RISK ASSESMENT AND DETERMINING CONTROL (HIRADC) PADA PROYEK PEMBANGUNAN MASJID RAYA AL-BAKRIE BANDAR LAMPUNG - Elian Zhafira; Rajiman, Rajiman (Yayasan Nusantara Hasana Berdikari, 2025)
One of the challenges in construction activities is occupational safety. Every work process often involves the use of heavy equipment, heavy and dangerous building materials, and the height of the building structure, which can increase the risk of work accidents. The number of work accidents in the last five years shows a reasonably high increase, with 32% of work accidents in Indonesia coming from the construction sector. This study aims to identify potential hazards and risks of work accidents, conduct risk assessments, and provide control efforts for the dangers in the Al-Bakrie Grand Mosque construction project in Bandar Lampung. The method used is HIRADC (Hazard Identification, Risk Assessment, and Determining Control). The hazard identification is based on literature studies, field observations, and interviews. Risk assessments are carried out to determine how high the risk is by filling out questionnaires by respondents, namely the frequency level questionnaire and the severity level questionnaire. The questionnaire was then processed using the severity index method and risk matrix sourced from PUPR Regulation No. 10 of 2021. The results of the analysis show that 35 hazard variables have the potential to cause work accidents. The risk assessment results obtained a low-risk category of 31 (88%) and a medium-risk category of 4 (12%). Control efforts must be carried out to eliminate or even reduce the risk of work accidents in the project by the control hierarchy, namely elimination, substitution, technical control, administrative control, and personal protective equipment (PPE).